Unusual manifestations of visceral leishmaniasis in children: a case series and its spatial dispersion in the western region of São Paulo state, Brazil - Luiz Euribel Prestes-Carneiro; Patricia Rodrigues Naufal Spir; Mateus Fontanesi; Karen Gabriella Pereira Garcia; Francisco Assis da Silva; Edilson Ferreira Flores; Dewton de Moraes Vasconcelos (BMC Infectious Diseases, 2019)
Abstract Background Visceral leishmaniasis (VL) is becoming endemic in São Paulo state, in the southeastern region of Brazil. Unusual manifestations with non-specific signs and symptoms may make diagnosis difficult and delay treatment, increasing the risk of severity and death, particularly in new endemic areas. There are few studies on patients with these characteristics in Brazil. We describe a case series of unusual manifestations of VL in children and its spatial dispersion in the western region of São Paulo state. Cases presentation From 2009 to 2014, five clinical cases involving children treated in the Regional Hospital of Presidente Prudente (RH) were selected. Two patients had multiple relapses requiring liposomal amphotericin B; one patient had VL-cytomegalovirus-dengue co-infection and liver injury; one patient was diagnosed with X-linked agammaglobulinemia, a primary immunodeficiency; and one patient was diagnosed with VL-human immunodeficiency virus/acquired immunodeficiency syndrome (VL-HIV/AIDS) co-infection. Primary or secondary immunodeficiencies were found in four children, and associated viral infections were found in three children. Three patients were referred from other hospitals to RH. With regard to the geographic spread of VL, more cases were found in the northern area, in the epicenter of the infection where the first cases were registered, flowing south; a spatial-temporal occurrence was found. Conclusions Primary and secondary immunodeficiencies and viral co-infectious should be considered among unusual manifestations of VL, especially in those with multiple relapses. Spatial-temporal occurrence was found. Thus, integrated actions and effective monitoring of the disease are needed to complement curative practices to stem the tide of the epidemic.